The Influence of Social Media and Financial Literacy on Decision to Use Shopee PayLater (Case Study of the Young Generation in Surakarta) - Fany Nur Zabrina; Suprihati; Dwi Septiana Wulandari; Nathania Regita Cahyani (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
For today’s young generation, Shopee PayLater makes it easy to make payment transactions. This research aims to determine the influence of financial literacy and social media on the decision to use Shopee Paylater among the young generation of Surakarta, Indonesia. This research is quantitative research. Using multiple linear regression analysis, through immersion tests, validity tests, reliability tests, classical assumption tests and F tests. The population in this study is the younger generation in Surakarta. The sample for this research was 60 samples. The results of this research show that financial literacy and social media both partially influence the decision to use Shopee Paylater.